The Influence of Succession Management and Performance Employee to Corporate Success (Analysis In PT Prisma Group) - Irzan Syahrial; Yetti Supriyati; Bedjo Sujanto (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
The purpose of this research is to understand comprehensively on the implementation of corporate success as a tool for the business world for formulating company policies that are very useful in the field of human resource management, by applying variables that have a large influence consisting of succession management and performance employee. The sample that was studies was 365 employees from the total population of the population of all PT Pisma Group employees which was divided into 5 subsidiaries as many as 4,204 employees were carried out in three company locations: Semarang, Pekalongan and Surabaya, using the questionnaire method in testing the data generated is valid and reliable. Data analysis techniques use quantitative methods with path analysis methods. This study concludes that corporate success is directly related to the existence of succession management and employee performance. Succession management requires that employee performance against the company be clear and measurable and cannot stand alone. Employee performance appraisal must be consistent and integrated with well-agreed succession management, so that the company is able to get reliable and prospective professional company leaders are able to support the company in the future to be very competitive, to the desired company success.